2011
DOI: 10.1103/physrevlett.107.215002
|View full text |Cite
|
Sign up to set email alerts
|

Electron Temperature Gradient Scale at Collisionless Shocks

Abstract: Shock waves are ubiquitous in astrophysics and interplanetary space. In collisionless plasmas they transform directed flow energy into thermal energy and accelerate energetic particles. The energy repartition amongst particle populations is a multi-scale process related to the spatial and temporal structure of the electromagnetic fields within the shock layer. While major features of the large scale ion heating are known, the electron heating and smaller scale fields remain poorly understood and controversial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 30 publications
7
81
3
Order By: Relevance
“…Zank et al (2001) suggested that these fine structures will help to circumvent the injection problem for Anomalous cosmic rays. In a very recent study, using Clusters observation, Schwartz et al (2011) showed that at Earth's bow shock half of the temperature occurred in about ∼7c/ω pe or ∼(1/7)c/ω pi . The total width of the shock in Schwartz et al (2011), which is close to L diff in our work, however, is another factor of ∼6 (see their Figure 3).…”
Section: Diffusive Shock Acceleration Of Electrons At a Finite-width mentioning
confidence: 99%
See 1 more Smart Citation
“…Zank et al (2001) suggested that these fine structures will help to circumvent the injection problem for Anomalous cosmic rays. In a very recent study, using Clusters observation, Schwartz et al (2011) showed that at Earth's bow shock half of the temperature occurred in about ∼7c/ω pe or ∼(1/7)c/ω pi . The total width of the shock in Schwartz et al (2011), which is close to L diff in our work, however, is another factor of ∼6 (see their Figure 3).…”
Section: Diffusive Shock Acceleration Of Electrons At a Finite-width mentioning
confidence: 99%
“…In a very recent study, using Clusters observation, Schwartz et al (2011) showed that at Earth's bow shock half of the temperature occurred in about ∼7c/ω pe or ∼(1/7)c/ω pi . The total width of the shock in Schwartz et al (2011), which is close to L diff in our work, however, is another factor of ∼6 (see their Figure 3). Therefore, in this work, we assume that the shock width is given by the ion inertial length scale L diff ∼ c/ω pi .…”
Section: Diffusive Shock Acceleration Of Electrons At a Finite-width mentioning
confidence: 99%
“…By their own calculation this underestimates the total electron temperature by a factor as large as 2. While they argue that the cadence required for full distributions, from which full moments could be calculated, would be much longer, it would be perfectly straightforward to calculate moments based on the 1-D distributions they have available (Schwartz et al [2011] call these pseudotemperatures). This point will not be developed further here, other than to note that increasing electron temperatures by a factor ∼ 2 would make the discrepancy in Mozer and Sundkvist [2013, Figure 6] much less pronounced.…”
Section: 1002/2013ja019624mentioning
confidence: 99%
“…It is now well known that coronal shocks can accelerate electrons (Schwartz et al 2011), protons (Park et al 2012), and ions (e.g., Giacalone 2005), giving origin to gradual bursts of extremely energetic particles, referred to as solar energetic particle (SEP) events, which generally have higher fluxes and harder energetic spectra (Cliver et al 2004) than impulsive SEPs produced in solar flares. Moreover, shocks propagating into the interplanetary space toward the Earth can carry a significant southward component of the magnetic field that can eventually reconnect with the Earth magnetosphere triggering electromagnetic disturbances at the ground (the so-called geomagnetic storms).…”
Section: Introductionmentioning
confidence: 99%